Biomedical Implications of Autophagy in Macromolecule Storage Disorders - Palhegyi, Adina Maria; Seranova, Elena; Dimova, Simona; Hoque, Sheabul; Sarkar, Sovan (Frontiers in Cell and Developmental Biology, 2019)
An imbalance between the production and clearance of macromolecules such as proteins, lipids and carbohydrates can lead to a category of diseases broadly known as macromolecule storage disorders. These include, but not limited to, neurodegenerative diseases such as Alzheimer’s, Parkinson’s and Huntington’s disease associated with accumulation of aggregation-prone proteins, Lafora and Pompe disease associated with glycogen accumulation, whilst lipid accumulation is characteristic to Niemann-Pick disease and Gaucher disease. One of the underlying factors contributing to the build-up of macromolecules in these storage disorders is the intracellular degradation pathway called autophagy. This process is the primary clearance route for unwanted macromolecules, either via bulk non-selective degradation, or selectively via aggrephagy, glycophagy and lipophagy. Since autophagy plays a vital role in maintaining cellular homeostasis, cell viability and human health, malfunction of this process could be detrimental. Indeed, defective autophagy has been reported in a number of macromolecule storage disorders where autophagy is impaired at distinct stages, such as at the level of autophagosome formation, autophagosome maturation or improper lysosomal degradation of the autophagic cargo. Of biomedical relevance, autophagy is regulated by multiple signalling pathways that are amenable to chemical perturbations by small molecules. Induction of autophagy has been shown to improve cell viability and exert beneficial effects in experimental models of various macromolecular storage disorders where the lysosomal functionality is not overtly compromised. In this review, we will discuss the role of autophagy in certain macromolecule storage disorders and highlight the potential therapeutic benefits of autophagy enhancers in these pathological conditions.